Maintenance of Functional Human Cancellous Bone and Human Hematopoiesis in NOD/SCID Mice - Frédérique Hubin; Chantal Humblet; Zakia Belaid; Roland Greimers; Jacques Boniver; Albert Thiry; Marie-Paule Defresne (Cell Transplantation, 2004)
Attempts were made to establish models to study interactions between marrow stromal cells and hematopoietic cells in vivo. The approach was to create a NOD-SCID-hu murine model of long-term human hematopoiesis by implantation of a human adult bone fragment. Nine to 12 weeks posttransplantation, human CD45+ cells were detected in the blood and the spleen of some mice. The histology of the human transplant showed that human bone fragment was viable at 9 weeks. Moreover, vessels of human origin, as assessed by immunohistochemical detection of human β 2 -microglobulin, were observed in the mouse tissue surrounding the transplanted human fragment.